Energy consumption optimization with PSO scheme for electric power steering system - Hanifah, Rabiatul A.; Toha, Siti Fauziah; Ahmad, Salmiah (International Association of Computer Science and Information Technology Press (IACSIT Press）, 2014)
Energy management in Electric Vehicle (EV) technology is very important as the energy source of all its system operations are solely relying on the battery. The unique characteristic of Electric Power Assist Steering (EPAS) system provides a way in realizing minimum energy consumption in EV subsystem. The controller in the EPAS system need to be tuned with the optimal performance setting so that less current is needed for its optimum operation. In this paper, Particle Swarm Optimization (PSO) algorithm is implemented as tuning mechanism for PID controller. The aim of this hybrid controller is to minimize energy consumption of the EPAS system in EV by minimizing the assist current supplied to the assist motor. The PSO searching method will search for the best gain parameters of the PID controller and providing the fast tuning feature that distinguish it from the conventional trial and error method. Simulation results shows the performance and effectiveness of using PSO algorithm for PID tuning.